MODY 2: Mutation identification and molecular ancestry in a Brazilian family - Mota, Adolfo J. [UNESP]; Brüggemann, Simone; Costa, Fabrício F. (Elsevier, 2013)
Maturity Onset Diabetes of the Young (MODY) is a heterogeneous group of genetic diseases characterized by a primary defect in insulin secretion and hyperglycemia, non-ketotic disease, monogenic autosomal dominant mode of inheritance, age at onset less than 25. years, and lack of auto-antibodies. It accounts for 2-5% of all cases of non-type 1 diabetes. MODY subtype 2 is caused by mutations in the glucokinase (GCK) gene. In this study, we sequenced the GCK gene of two volunteers with clinical diagnosis for MODY2 and we were able to identify four mutations including one for a premature stop codon (c.76C>T). Based on these results, we have developed a specific PCR-RFLP assay to detect this mutation and tested 122 related volunteers from the same family. This mutation in the GCK gene was detected in 21 additional subjects who also had the clinical features of this genetic disease. In conclusion, we identified new GCK gene mutations in a Brazilian family of Italian descendance, with one due to a premature stop codon located in the second exon of the gene. We also developed a specific assay that is fast, cheap and reliable to detect this mutation. Finally, we built a molecular ancestry model based on our results for the migration of individuals carrying this genetic mutation from Northern Italy to Brazil. © 2012 Elsevier B.V.
Keywords: Brazilian family; Glucokinase (GCK); MODY2; New mutations; glucokinase; adult; amplicon; clinical article; clinical feature; controlled study; correlation analysis; exon; gene identification; gene location; human; molecular genetics; mutational analysis; non insulin dependent diabetes mellitus; pedigree analysis; polymerase chain reaction; priority journal; restriction fragment length polymorphism; sequence analysis; stop codon; Adult; Brazil; Child; Codon, Terminator; Diabetes Mellitus, Type 2; Emigration and Immigration; Exons; Female; Glucokinase; Humans; Italy; Male; Models, Genetic; Mutation; Polymerase Chain Reaction; Polymorphism, Restriction Fragment Length